Repertório vocal e variações no canto de Basileuterus spp. (Passeriformes, Parulidae) em fragmentos de mata (Uberlândia, MG) - Carvalho, Liliane Souza Dantas de (2010)
Bird s vocalization is directly related with vital behaviors. Some species are very sensitive to changes in sound characteristics of vocalizations. The Oscine Passerines, because they have more complex syrinx and vocal learning capacity, are one of the group with higher possibility of present variation in their voice. This study selected three sympatric and partially syntopic of Oscine Passerines, Parulidae: Flavescent Warbler (Basileuterus flaveolus), White-bellied Warler (B. hypoleucus) and White-striped Warbler (B. leucophrys) aiming to characterize the vocal repertoire of Basileuterus spp., and whether these species alter the vocal parameters of their songs with the factors seasonality, distribution of fragments and the environmental noise. The study was conducted in Uberlândia, MG, in fragments of semideciduous forest in the Cerrado. In characterizing the vocal repertoire and to verify the effect of seasonality, was analyzed recordings made in the dry and rainy, and the other studies, was analyzed the data of the rainy season. In the analysis of vocal variation, we used only the songs, because of its importance to reproduction. The parameters tested were number of notes, duration of song, lowest and highest frequency, frequency range, peak-frequency and song rate. The vocal repertoire was varied among the species studied, B. flaveolus repertoire has one song and one call and B. hypoleucus repertoire has one song and three calls. Basileuterus leucophrys repertoire was the largest and most complex, with two songs and nine calls, including some simultaneous emission of sounds with different characteristics originating on either side of the syrinx (two-voice). Most of the vocal parameters of each species are similar to reviously in the literature to the microhabitats occupied by them. All species altered their vocalizations according to factors established and showed characteristic songs for each level of the factors tested. Thus, is possible to conclude that the three species of Basileuterus spp. have vocal repertoire of varied size and complexity, and in front of natural and antropogenic factors, these species are able to vary their vocalizations.